Study of GHG emissions in Brazil from 1990 to 2030 using system dynamics for simulation - Gallegos, Raphael (Revista Brasileira de Engenharia de Biossistemas, 2022)
This work studied five sectors which are responsible for GHG emissions in Brazil, namely: Agriculture, Energy, Land-use Change, Industrial Processes, and Waste. In addition to emissions, the Brazilian National Energy Balance was studied to understand the relationship between the energy matrix and GHG emissions. This entire study was developed using the System Dynamics methodology and, at the end, two scenarios were proposed. In the first scenario, it is possible to observe how GHG emissions are distributed in Brazil, while in the second scenario, it is possible to observe a reduction of about 48.9% of emissions in the country, related to the reduction of Land-use Change and Forestry together with the Energy Sector.